2012
DOI: 10.12681/mms.297
|View full text |Cite
|
Sign up to set email alerts
|

Environmental properties of the southern Gulf of Aqaba, Red Sea, Egypt

Abstract: Environmental properties (temperature, dissolved oxygen, nutrients and chlorophyll a) of the epipelagic zone off Sharm El-Sheikh, Red Sea, Egypt were studied seasonally throughout a year from March 1995 to March 1996. Water samples were collected from five water depths (0, 25, 50, 75 & 100 m). The studied parameters exhibited clear seasonal variability along the water column. The vertical distribution of water temperature showed thermal homogeneity during most seasons, and thermal stratification in summer. Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
4
3
0
Order By: Relevance
“…Temperatures recorded during the current study for the second period (2015-2016) were in agreement with results of previous records at the Red Sea as Abdelmongy and El-Moselhy (2015), who recorded a summer temperature of 29.25 o C and a winter temperature of 17.96 o C, 28.2 o C at summer and 20.17 at winter (Madkour, 2013) and 30.5 o C at summer and 22.8 o C at winter (Dorgham et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Temperatures recorded during the current study for the second period (2015-2016) were in agreement with results of previous records at the Red Sea as Abdelmongy and El-Moselhy (2015), who recorded a summer temperature of 29.25 o C and a winter temperature of 17.96 o C, 28.2 o C at summer and 20.17 at winter (Madkour, 2013) and 30.5 o C at summer and 22.8 o C at winter (Dorgham et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…DO in the study area is almost similar to the recorded DO in other regions of Red Sea [69,70]. DO concentration of south part of Gulf of Aqaba, Red Sea, Egypt is 6.6-7 mgL −1 which was reported the same as in the surface water [71]. The minor variations of physicochemical characteristics including salinity, pH, and DO were found by this study.…”
Section: Seawater Characteristicssupporting
confidence: 86%
“…In a study of bio-optics along the axis of the Gulf, Stambler (2005) found that the concentrations of Chl a remained consistently less than 0.4 µg L −1 . Dorgham et al (2012) determined the concentrations of Chl a down to 100 m at a coastal station (Sharm El-Sheikh) at the Strait of Tiran over an annual cycle and observed that the concentrations ranged from 0.1 to 0.33 µg L −1 . The only instance when they were high (up to 1.2 µg L −1 ) was in the spring at depths >70 m.…”
Section: Gulf Of Aqabamentioning
confidence: 99%